International handbook of accounting education and certification - Anyane-Ntow, Kwabena (Pergamon Press, 1992)
This is the first work of its kind. Original contributions from leading academicians, practitioners and accounting associations from around the world make this handbook a unique source of information on international accounting education and certification processes. A uniform format in most of the chapters allows for easy comparison between countries. This volume documents the development of accounting education and practice at country and global levels; studies the sensitivity of accounting education and practices to the unique socio-economic needs of its environment; and allows comparative studies at a time when attempts have begun to harmonize accounting education internationally. Most importantly, it shows how educational programmes around the world are preparing future accounting professionals to deal with the rapid technological and environmental changes of the 21st century.